Diphtheric encephalitis and brain neuroimaging features. (November 2017) - Foo, Jen Chun; Rahmat, Kartini; Mumin, Nazimah Ab; Koh, Mia Tuang; Gan, Chin Seng; Ramli, Norlisah; Fong, Choong Yi
Highlights: First report of brain MRI features due to diphtheric encephalitis. Expands the neurological features associated with diphtheric encephalitis. Our report highlight the importance of neuroimaging findings in diagnosing diphtheric encephalitis. Abstract: We report a rare case of paediatric diphtheria complicated with encephalitis. A 6-year-old boy who did not receive his scheduled diptheria–tetanus–pertusis vaccination presented with one episode of generalised convulsive seizure. His illness was preceded by a 3 day history of fever associated with enlarged exudative tonsils with a pseudomembrane. He was commenced on intravenous penicillin and oral erythromycin. However, he developed progressive encephalopathy with focal neurological deficit which required intubation on day 5 of illness. Throat swab polymerase chain reaction for diphtheria toxin A and B were positive and diphtheria antitoxin was given. Magnetic resonance imaging (MRI) of brain showed T2-weighted hyperintensities over the anterior cingulate gyri, insular cortex and cerebellum. This is the first reported MRI finding of diphtheric encephalitis. Our report highlights the importance of neuroimaging in diagnosing diphtheric encephalitis particularly in cases with unremarkable cerebrospinal findings.